Keterlibatan masyarakat pada radio komunitas untuk pengurangan risiko bencana - Irene Santika Vidiadari; Caecilia Santi Praharsiwi; Mario Antonius Birowo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This paper discusses participatory communication for disaster risk reduction through community radio. Community radio is managed independently by volunteers. This research uses a case study approach: interviews, FGDs, and document studies on community radio collected data. The results show that community radio plays an essential role at each stage of disaster management. In addition, community radio is also engaged in increasing the capacity of the community by providing needed information, such as information on agriculture and sports. Stakeholders who play a role in community radio consist of volunteers, the community, government, and non-governmental organizations. Volunteers and residents play a role in running community radio, and the government, through the disaster management agency, provides factual information about disasters. Non-Governmental Organizations play a role by providing training for volunteers. Community radio has financing, equipment maintenance, and volunteer regeneration challenges. Various efforts need to be made by all stakeholders to face these challenges.